KIDNEY INFECTION – SYMPTOMS, TREATMENT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Kidney cold is understood as various inflammatory processes of kidney tissues that occur under the influence of cold. Low temperatures cause a strong narrowing of blood vessels, which makes it difficult for oxygen, nutrients and other necessary components to pass through. The result is cell death or dysfunction.